Biochar properties and soil type drive the uptake of macro‐ and micronutrients in maize (Zea mays L.). Issue 2 (2nd January 2019) - Bornø, Marie Louise; Müller-Stöver, Dorette Sophie; Liu, Fulai
Abstract: The use of biochar in agriculture is a promising management tool to mitigate soil degradation and anthropogenic climate change. However, biochar effects on soil nutrient bioavailability are complex and several concurrent processes affecting nutrient bioavailability can occur in biochar‐amended soils. In a short‐term pot experiment, the concentration of N, P, K, S, Ca, Mg, Cu, Zn, Mn, B, Fe, and Na in the shoots of maize grown in three different soil types [sandy soil (S1), sandy loam (S2), and sandy clay loam (S3)] was investigated. The soils were either unamended or amended with two different biochars [wheat straw biochar (SBC) or pine wood biochar (WBC)] at two P fertilizer regimes (–/+ P). We used three‐way ANOVA and Principal Component Analyses (PCA) of transformed ionomic data to identify the effects of biochar, soil, and P fertilizer on the shoot nutrient concentrations. Three distinct effects of biochar on the shoot ionome were detected: (1) both biochars added excess K to all three soils causing an antagonistic effect on the uptake of Ca and Mg in maize shoots. (2) Mn uptake was affected by biochar with varying effects depending on the combined effect of biochar and soil properties. (3) WBC increased maize uptake of B, despite the fact that WBC increased soil pH and added additional calcite to the soil, which would be expected to reduce B bioavailability. The results of this study highlight the fact that the bioavailability of several macro and micronutrients is affected by biochar application to soil and that these effects depend on the combined effect of biochar and soils with different properties.